Conception and characterisation of a novel 5_Shaped antenna for 5G application using WCIP method - El Hadri, Doae; Zugari, Asmaa; Zakriti, Alia (Australian journal of electrical & electronics engineering, 2021)
In this paper, a novel 5_Shaped antenna for fifth generation (5 G) is presented. The proposed antenna is printed on a FR4 substrate with a compact size of 13 × 12.8 mm 2 . It has a high gain of 6.97 dB and good radiation efficiency of 84% at 28 GHz band. The impedance bandwidth of the presented antenna is about 9.67% (26.52-29.23 GHz) that is useful for the 5 G applications. The aim of this work is the characterisation of a novel antenna using a fast numerical method Wave Concept Iterative Procedure (WCIP). The proposed antenna has been designed and optimised using electromagnetic simulation software CST MS. The theoretical formulation of WCIP method is based on two relationships that bind waves, one in the spatial domain and the other in the spectral domain. The transition of waves between the two domains is effected by the Fast Modal Transform (FMT). The simulated and numerical results for the reflection coefficient and VSWR parameter are in good accord. In addition, a comparison in the computing time shows that the iterative method is faster by a factor of 5.85 than CST Simulator. The radiation pattern, realised gain and efficiency of the 5_shaped antenna are also obtained.